Comparison of immune checkpoint inhibitor-induced arthritis and reactive arthritis to inform therapeutic strategy: review - Jensen, Anders Kirkegaard; Chatzidionysiou, Katerina; Torp, Christopher Kirkegaard; Sørensen, Anne Sofie; Tenstad, Helene Broch; Schäfer, Valentin S.; Kostine, Marie; Jacobsen, Søren; Leipe, Jan; Kragstrup, Tue Wenzel (Biomedicine & pharmacotherapy, 2022)
Introduction - Immune checkpoint inhibitor-induced inflammatory arthritis (ICI-IA) is a relatively new disease entity caused by ICI agents during cancer therapy. Reactive arthritis (ReA) is a well-known disease entity caused by urogenital or gastrointestinal bacterial infection or pneumonia. In this sense, ICI-IA and ReA are both defined by a reaction to a well-specified causal event. As a result, comparing these diseases may help to determine therapeutic strategies. - Methods - We compared ICI-IA and ReA with special focus on pharmacological management. Specifically regarding treatment, we conducted a literature search of studies published in the PubMed database. Inclusion criteria were studies on treatment with non-steroidal anti-inflammatory drugs (NSAIDs), glucocorticoids (GC), or disease modifying antirheumatic drugs (DMARDs) in ICI-IA or ReA. During systematic selection, 21 studies evaluating ICI-IA and 14 studies evaluating ReA were included. - Results - In ICI-IA, prospective and retrospective studies have shown effects of non-steroidal anti-inflammatory drugs (NSAIDs), glucocorticoid (GC), sulfasalazine (SSZ), methotrexate (MTX), hydroxychloroquine (HCQ) and TNFi. In ReA, retrospective studies evaluated NSAIDs and GC. A randomized controlled trial reported the effect of SSZ, and a retrospective study reported the effect of MTX and SSZ in combination with tumor necrosis factor alpha inhibition (TNFi). For both entities, small case reports show treatment effects of interleukin 6 receptor inhibition (IL-6Ri). - Discussion - This literature review identified both similarities and differences regarding the pathogenesis and clinical features of ReA and ICI-IA. Studies on treatment reported effectiveness of NSAIDs, GC, MTX, SSZ and TNFi in both diseases. Further, small case reports showed effects of IL-6Ri.
Online verfügbar: 25. Februar 2022, Artikelversion: 25. Februar 2022
Gesehen am 18.03.2024